Pin1 Is Regulated by CaMKII Activation in Glutamate-Induced Retinal Neuronal Regulated Necrosis - Wang, Shuchao; Liao, Lvshuang; Huang, Yanxia; Wang, Mi; Zhou, Hongkang; Chen, Dan; Liu, Fengxia; Ji, Dan; Xia, Xiaobo; Jiang, Bing; Huang, Jufang; Xiong, Kun (Frontiers in Cellular Neuroscience, 2019)
In our previous study, we reported that peptidyl-prolyl isomerase 1 (Pin1)-modulated regulated necrosis (RN) occurred in cultured retinal neurons after glutamate injury. In the current study, we investigated the role of calcium/calmodulin-dependent protein kinase II (CaMKII) in Pin1-modulated RN in cultured rat retinal neurons, and in an animal in vivo model. We first demonstrated that glutamate might lead to calcium overloading mainly through ionotropic glutamate receptors activation. Furthermore, CaMKII activation induced by overloaded calcium leads to Pin1 activation and subsequent RN. Inactivation of CaMKII by KN-93 (KN, i.e., a specific CaMKII inhibitor) application can decrease the glutamate-induced retinal neuronal RN. Finally, by using an animal in vivo model, we also demonstrated the important role of CaMKII in glutamate-induced RN in rat retina. In addition, flash electroretinogram results provided evidence that the impaired visual function induced by glutamate can recover after CaMKII inhibition. In conclusion, CaMKII is an up-regulator of Pin1 and responsible for the RN induced by glutamate. This study provides further understanding of the regulatory pathway of RN and is a complementary mechanism for Pin1 activation mediated necrosis. This finding will provide a potential target to protect neurons from necrosis in neurodegenerative diseases, such as glaucoma, diabetic retinopathy, and even central nervous system diseases.